Analisis Keberadaan Manifestasi Panas Bumi Terhadap Keseimbangan Lingkungan Sekitar Desa Talawaan Bantik - Angelika Kristi Nilahi; Cyrke Adfie Netty Bujung; Jeilen Gabriela Nikita Nusa; Alfrie Musa Rampengan (Jurnal FisTa : Fisika dan Terapannya, 2024)
Energy is very important for humans, apart from that the environment also has the same important role, in other words energy and the environment are inseparably linked. This research aims to see the differences in the chemical content and physical properties of geothermal manifestation water and residents’ well water, as well as to find outh whether the manifestation water content affects local residents’ well water. The research samples consisted of hot springs and local well water, where the physical and chemical properties observed were: Temperature, pH, DHL, CL, Fe, H2S,SO4. The results of measurement and sample testing obtained were then analyzed descriptively. The result obtained from this research are that for the physical properties and chemical content of Cl, Fe, H2S, and SO4 there is not much difference in the content analysis results, while for the DHL, Temperature and pH values there are quite large differences, but still is below the standard value for clen water quality.